Odpowiedzi

2010-04-11T16:05:17+02:00
A) h= a√3/2
h=12√3 /2
h= 6√3
b) h=2√3/2
h=√3
c) h=4√6/2
h=2√6
d) h= a√3/2
12= a√3/2 /*2
24= a√3 /:√3
24/√3=a
e) 3√3=a√3/2 /*2
6√3=a√3 / :√3
6=a
f) 2√21= a√3/2 /*2
4√21=a√3 /:√3
4√7=a
1 2 1
Najlepsza Odpowiedź!
2010-04-11T16:12:42+02:00
A) a = 12 . h= ?
h=12√3:2=6√3
P=(6√3)²√3:4=27√3
b) a = 2√3 , h= ?
h=2√3*√3:2=3
P=2√3*3:2=3√3
c)a = 4√6, h= ?
h=4√6*√3:2=6√2
P=4√6*6√2:2=12√12=24√3
d) h = 12, a = ?
12=a√3:2 /*2
24=a√3 /:√3
a=8√3
P=8√3*12:2=48√3
e) h= 3√3, a= ?
3√3=a√3:2 /*2
6√3=a√3 /:√3
a=6
P=6*3√3:2=9√3
f) h= 2√21, a= ?
2√21=a√3:2 /*2
4√21=a√3 /:√3
4√7=a
a=4√7
P=4√7*2√21=8√147